2021
DOI: 10.1029/2020jf005741
|View full text |Cite
|
Sign up to set email alerts
|

Snow Avalanche Detection and Source Constraints Made Using a Networked Array of Infrasound Sensors

Abstract: The detection and study of rapid gravity-driven mass movements using infrasound is a growing area of research and includes studies of hazardous flows like lahars (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The seismic source locations are in better agreement with the location of coarse‐grained PDC deposits than the fine‐grained PDC deposits (Figure 4). By comparison with other surficial mass movements such as debris flows and snow avalanches (Allstadt et al., 2018; Johnson et al., 2021; Marchetti et al., 2020; Watson et al., 2021; Zhang et al., 2021), PDC seismic signals are thought to be generated by the dense basal flow exerting forces on the solid Earth. Hence, the seismic‐derived PDC source locations are likely to be more closely related to the coarse‐grained deposits than the fine‐grained deposits that are derived from the dilute cloud of hot gas and ash that surrounds the dense basal flow.…”
Section: Discussionmentioning
confidence: 99%
“…The seismic source locations are in better agreement with the location of coarse‐grained PDC deposits than the fine‐grained PDC deposits (Figure 4). By comparison with other surficial mass movements such as debris flows and snow avalanches (Allstadt et al., 2018; Johnson et al., 2021; Marchetti et al., 2020; Watson et al., 2021; Zhang et al., 2021), PDC seismic signals are thought to be generated by the dense basal flow exerting forces on the solid Earth. Hence, the seismic‐derived PDC source locations are likely to be more closely related to the coarse‐grained deposits than the fine‐grained deposits that are derived from the dilute cloud of hot gas and ash that surrounds the dense basal flow.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is needed to accurately model the infrasound generation from surficial mass movements (cf. Coco et al 2021;Johnson et al 2021) so that infrasound observations can be reliably used to quantitatively constrain flow properties and improve hazard mitigation efforts. In tandem, methods to detect potentially weak signals of surficial mass movements within realistic persistent and variable background noise must continue to be developed to achieve robust monitoring capabilities (Sanderson et al 2021).…”
Section: Volcanic Sourcesmentioning
confidence: 99%
“…While many anthropogenic and volcanic explosions appear to be well-characterized by a simple volumetric source, more complex sources including buried chemical explosions (e.g., Blom et al, 2020;Kim et al, 2020), complex volcanic explosions (e.g., Iezzi et al, 2019;Johnson et al, 2008;Jolly et al, 2017), or mass movements (e.g., Johnson et al, 2021) may require a directional source component. Unfortunately, most infrasound sensors are placed on Earth's surface, thus the full acoustic radiation pattern in field studies is not adequately sampled (e.g., Matoza et al, 2013).…”
Section: Acoustic Directionalitymentioning
confidence: 99%
“…Multipole inversions allow for a more in depth understanding of potentially directional acoustic sources such as those from complex volcanic explosions (e.g., Iezzi et al, 2019;Johnson et al, 2008;Jolly et al, 2016Jolly et al, , 2017, buried chemical explosions (e.g., Blom et al, 2020;Kim et al, 2020), and mass movements (e.g., Johnson et al, 2021). Recent studies (e.g., Blom et al, 2020;Kim et al, 2020) have found that acoustic wavefields created by underground explosions have strong vertical directionality which cannot be accounted for by a simple monopole source.…”
Section: Application Of Inversions To the Topography Of Yasur Volcano...mentioning
confidence: 99%